Aspirin and Acetaminophen Use and the Risk of Cervical Cancer. Issue 3 (July 2015) - Friel, Grace; Liu, Cici S.; Kolomeyevskaya, Nonna V.; Hampras, Shalaka S.; Kruszka, Bridget; Schmitt, Kristina; Cannioto, Rikki A.; Lele, Shashikant B.; Odunsi, Kunle O.; Moysich, Kirsten B.
Abstract : Objective: In this study, we investigated whether regular use of aspirin or acetaminophen was associated with risk of cervical cancer in women treated at an American cancer hospital. Methods: This case-control study included 328 patients with cervical cancer and 1, 312 controls matched on age and decade enrolled. Controls were women suspected of having but not ultimately diagnosed with a neoplasm. Analgesic use was defined as regular (at least once per week for ≥6 months), frequent (≥7 tablets/week), very long term (≥11 years), or frequent, long term (≥7 tablets per week for ≥5 years). Results: Compared to nonusers, frequent aspirin use was associated with decreased odds of cervical cancer (odds ratio, 0.53; 95% confidence interval, 0.29-0.97). A slightly larger association was observed with frequent, long-term use of aspirin (odds ratio, 0.46; 95% confidence interval, 0.22-0.95). Acetaminophen use was not associated with the risk of cervical cancer. Conclusions: Our findings suggest that frequent and frequent, long-term use of aspirin is associated with decreased odds of cervical cancer. To our knowledge, this is the first US-based study examining these associations. Given the widespread use of nonsteroidal anti-inflammatory drugs and acetaminophen worldwide, further investigations of the possible role of analgesics in cervical cancer, using a larger sample size with better-defined dosing regimens, are warranted. Abstract : Frequent and frequent, long-term use of aspirin may be associated with reduced risk of cervical cancer.